SPECIFICS OF SUBFRACTIONAL SPECTRUM OF APOLIPOPROTEIN B RELATED LIPOPROTEINES IN CAROTID OR CORONARY ATHEROSCLEROSIS PATIENTS - N. E. Gavrilova; V. A. Metelskaya; I. N. Ozerova; E. B. Yarovaya; S. A. Boytsov (Российский кардиологический журнал, 2016)
Apolipoprotein (apo)B-containing lipoproteines of low density are heterogeneous by their nature, and differ by their lipid and protein contents, charge, particle size and functional activity. High blood level of small dense particles of low-density lipoproteines (LDL) is related to higher risk of coronary heart disease 3-5 times irrelevant to cholesterol level they contain.Aim. To evaluate and describe the specifics of subfraction spectrum of apo-Bcontaining lipoproteines in patients with lesions in carotid and/or coronary circulation.Material and methods. Totally, 310 patients included (62,5±9,3 year old), underwent duplex scanning of carotid arteries and coronary arteriography (M/F 203/107). Sub fraction spectrum of lipoproteines was assessed with electrophoresis on 3% polyacrylamide gel (Lipoprint system, Quantimetrix Lipoprint LDL System, USA). The level of severity of coronary atherosclerosis lesion was assessed with the Gensini Score (GS).Results. Evaluation of subfractional spread of lipoproteines according to the results of duplex scan showed that in the group of patients with intima-media thickness (IMT) >0,9 mm part of intermediate density lipoproteides (IDL) C is higher (11,0±3,6 vs 9,1±2,8%, р=0,002), and the part of low density lipoproteides (LDL) 1 is lower (16,7±4,1 vs 18,1±3,7%, р=0,047) comparing to the patients with normal IMT. Assessment of the spread of LDL subfractions according to the number of atherosclerotic plaques (AP) and/or lesion of carotid arteries showed that among the patients with ≥3 AP and/or involved carotid arteries for >45%, the part of LDL C decreased (9,9±3,2 vs 11,4±3,7%, р=0,003), but there is increase of intermediate density lipoproteides A (IDL A) (9,3±2,6 vs 8,4±2,5%, р=0,013) and large particles of IDL 1 (17,8±4,0 vs 16,2±4,0%, р=0,005) and comparing to those having <3 AP and/or in lesion ≤45%. With the grading score GS the groups of patients were selected with absence of coronary atherosclerosis (GS =0, n =68) and presence of coronary atherosclerosis (GS >0, n=242). Coronary patients were selected to subgroups with minimal or mild (GS <35, n =81) and severe lesion of coronary arteries (GS ≥35, n=161). In the group of GS >0 part of very low density lipoproteines (VLDL) (21,0±4,1 vs 19,3±4,1%, р=0,004) and IDL (11,4±3,4 vs 10,5±3,3%, р=0,047) were higher, and part of IDL A (8,4±2,5 vs 9,4±2,6%, р=0,006) and large particles IDL 1 (16,8±4,2 vs 18,2±4,2%, р=0,013) lower than group GS =0. In the group GS ≥35 the part of IDL C was significantly higher comparing to those from GS <35 (11,8±3,7 vs 10,8±3,0%, р=0,008). According to multifactor regression, the risk of coronary atherosclerosis is related to higher part of VLDL (OR =1,1, 95% CI 1,0-1,2, р=0,039), small dense particles of LDL 3-6 (OR =1,3, 95% CI 1,0-1,6, р=0,049), and higher part of LDL 2 is associated with the risk of coronary atherosclerosis by 10% GS score (OR =0,9, 95% CI 0,8-1,0, р=0,014). Conclusion. Combination of carotid and coronary arteries is related to the changes of subfractional lipoproteides spectrum (lower part of IDL A and large particles of LDL 1 and higher part of VLDL), characteristic for isolated lesion of coronary arteries regardless its prominence, which probably might be regarded as additional markers of atherogenity of lipid profile in earlier stage carotid and any coronary atherosclerosis.